(untitled) (Journal of Humanities and Social Sciences Research, 2023)
And since motor learning is one of the sciences that played a major role in developing the levels and mathematical skills of the players, and the transmission of the impact of learning, which is one of the important methods in learning in general and motor learning in particular, and in order for the benefit of the transmission of the impact of learning to be positive, it requires access to learning Performing the first skill to a good level until the effect of learning it is transferred to the other skill. Therefore, it was necessary to use educational methods that accelerate the learning process through the two researchers doing some exercises for the students by serving in tennis, which is a skill similar to the dropped blow in badminton in order to contribute to the acceleration of learning this skill for the students. The research aimed to identify the effect of the transmission of learning between the two skills of serving in tennis and the front drop kick in badminton for first-stage female students. The researcher used the experimental approach by designing an equal group with a pre and post-test. The frontal projection of female students in badminton, as well as the existence of a transfer of the impact of learning from learning to serve in tennis to learning the forward projection strike of female students in the first stage in badminton.